Tabungan Emas dalam Tinjauan Hukum Islam (Studi Kasus di Pegadaian Syariah Cabang Pinrang) - Khaerul Aqbar; Aswar, Aswar; Muh. Sepriadi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aims to determine the practice of product contracts and a review of Islamic law on gold savings products in Sharia pawnshops. The research method used a field research approach (filed reaserch) which was qualitative descriptive, and data collection was obtained through observation, interviews and library research (library reaserch), and the research locus was carried out at the Pinrang Syariah Pegadaian Branch. The research results found that; First, regarding the practice, the Pinrang Branch of the Sharia Pegadaian provides many facilities for customers who want to start investing in gold. In addition, Pegadaian Syariah also offers products in the form of Gold Savings, which is a gold buying and selling service with deposit facilities. As for the process of liquidating (selling) gold, it is carried out in two ways, namely by reselling it if the customer wants cash and printing if the customer wants it in the form of gold bullion. Second, the Gold Savings scheme in Sharia Pawnshops is a problematic contract because one of the contracts has an element of usury, to be precise in the murabahah contract, where scholars have different opinions about its abilities. Jumhur ulama agree on the prohibition (because some scholars from syafi'iyyah and malikiyyah argue that gold is included as á¹¡aman (price, means of payment, money) which cannot be exchanged in installments, because it causes usury and must be done in cash at the time of the contract. Third, DSN MUI and other contemporary scholars consider that the sale and purchase of gold / murabahah gold is permissible both in cash and credit as long as they are not intended as security (price) but sil'ah (goods).